Cyberhate Analysis Toward Gus Miftah on Social Media X: A Semiotic Perspective - Hartariansyah, Afrizal (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This study aims to examine cyberhate against Gus Miftah through Roland Barthes' semiotic approach, which includes analysis at the denotative, connotative, and mythical levels. Data consisting of 15 comments from social media platform X were analyzed qualitatively to identify the explicit and implicit meanings as well as the ideology contained in the speech. The findings reveal that the cyberhate directed at Gus Miftah is not only emotional in nature but also reflects the reproduction of social myths regarding the figure of the ulama, the sanctity of pesantren lineage, and resistance to forms of da'wah perceived as profane or commercial. Thus, this cyberhate represents a conflict of values in digital society between traditional norms and contemporary religious practices.